Sustainability reporting in the supermarket industry in the United Kingdom: a critical analysis - Anam-Skorczewska, Liliana (2007)
The dissertation investigates the state of affairs in non-financial reporting in the supermarket industry in the United Kingdom, aiming in evaluation and then development of recommendations which could improve this reporting.